Learning environments with different levels of technological engagement: a comparison of game-based, video-based, and traditional instruction on students' learning. Issue 8 (17th November 2021) - Chen, Yen-Chieh; Lu, Yu-Ling; Lien, Chi-Jui
ABSTRACT: Students' engagement in a learning environment has been a crucial factor in evaluating the quality of learning and predicting their academic success. With technologies being more applied in science education for enhancing learning engagement, it is important to study how learning environments with different levels of technological engagement (LTEs) affect students' learning. Data were collected from 168 fourth-grade students, ages 9–10, divided into 3 groups of different learning environments: (1) game-based instruction (high LTE) and (2) video-based instruction (medium LTE) as the two experimental groups, and (3) traditional instruction (low LTE) as the control group. Students' learning was monitored with two tests: scientific concept test and the scientific argumentation skills test. Descriptive and inferential statistics including t -test, ANCOVA, and the Johnson-Neyman procedure were used to examine how different LTEs affect students' learning as a group and by level (high-, medium-, and low-achieving). Findings demonstrated that (a) three forms of technology-supported learning significantly improve students' scientific knowledge and argumentation skills; (b) higher LTEs lead to significantly better learning of scientific knowledge, except for some high-achieving students who can learn equally well in traditional instruction; and (c) higher LTEs lead to significantly better learning of argumentation skills across all students.